Investigation of power transfer efficiency: utilizing different coil designs in wireless charging of electric vehicles - M. E. Thein; J. Charoensuk; M. Masomtob; W. Onreabroy; A. Kaewpradap (My University, 2021)
Abstract EV battery can be wirelessly charged by inductive coupling method between two electromagnetic couplers. In this study, the transmitter and receiver coils are designed. The effect of the number of turns for transmitter and receiver coils are studied. The results show that efficiency is decreased with the reduction of turns for both coils. Next, the spacing between each turn of coils is analyzed by 1mm of increasing for each simulation and the increased efficiency is only 2.6% for every 1mm spacing. Then, the power transfer efficiency is investigated for different coil designs. The efficiency can be improved with the proper consideration of air gap length, operation frequency, suitable coil designs and coil properties. Five coil designs such as circular, rectangular, double-D, double-D quadrature (DDQ) and bipolar designs are selected. The best design for maximum power transfer efficiency is DDQ design but the structure is complex since more wires are used in this design. The air-gap length between two coils is selected as 120mm and frequency is 85 kHz in this study.
Keywords: Wireless Power Transfer; Air gap (plumbing); Inductive coupling; Coil noise; Wireless Power Transfer Systems